Total electron content (TEC) and estimation of positioning error using Malaysia data / Y. Norsuzila ... [et al.] - Ya'acob, Norsuzila; M., Abdullah; M., Ismail; Z., Zakaria (2010)
This paper studied the TEC value for Malaysia regions, based on location of the receivers (latitude, longitude, height). The 13 location of GPS receiver stations across east and west Malaysia were chosen and their TEC values were compared. The determination of the TEC value in ionosphere is done using leveling process. In the process, the error translated from code-delay to the carrier-phase is assessed to reduce carrier phase ambiguities from the data. The positioning error can be calculated as one unit of TEC introduces a range error of approximately 0.16 meters at the L1 (1.6 GHz) frequency of GPS. From the results, the calculated TEC range errors were from -3.1 meters to 7.2 meters at different receiver locations.